Moral Outrage, Sticky Crisis, dan Strategi Komunikasi Krisis Pertamina Studi Kasus Skandal Korupsi dan Pengoplosan BBM - Jayanto, Dian (Communicology: Jurnal Ilmu Komunikasi, 2025)
Pertamina's crisis in 2025, triggered by the corruption scandal in raw oil procurement and the illegal practice of fuel blending, was a crisis that triggered public moral outrage. This research analyzes Pertamina's crisis communication strategy in responding to demands for transparency and justice, focusing on the effectiveness of the Situational Crisis Communication Theory (SCCT) approach expanded by Coombs & Tachkova (2024). The research method used a qualitative intrinsic case study through content analysis of Pertamina's press conference transcripts and online media coverage during the critical phase of the crisis (February-March 2025). The results show that Pertamina combined optimal strategies (apology, transparency of fuel test results, stakeholder engagement) with suboptimal strategies (denial, minimizing the scale of the crisis, and delayed response). This combination worsened the crisis dynamics, where denial and late response deepened value incongruence, while apology without explicit acknowledgement of moral transgression failed to reduce public outrage. Key findings suggest that the crisis persisted not only due to technical complexity, but also due to intense public emotions, triggered by perceptions of systemic injustice and greedy practices. The theoretical implications of the research emphasize the need for integration of moral dimensions in crisis communication frameworks, such as acknowledgement of ethical violations and reconciliation of values, as well as the importance of holistic responses that combine structural reforms with public empathy. This research makes a significant contribution to understanding the interplay between emotions and morals, particularly in the context of organizations facing sticky crises.